Are They Celebrity Followers? Examining the Third-Person Perception of Celebrity-Endorsed Advertising. (4th March 2018) - Pan, Po-Lin; Meng, Juan
ABSTRACT: This study explored how consumers' presumed influences mediated the impacts of source credibility and advertising skepticism on purchase intention in the context of celebrity-endorsed advertising (CEA). A national media consumer panel (N = 445) indicated the third-person perception (TPP) were positively correlated to celebrity expertise and attractiveness, but negatively influenced by advertising skepticism. Moreover, three celebrity credibility variables and advertising skepticism yielded direct effects on purchase intention. Indirect effects by the TPP were also generated on purchase intention. The TPP would mediate the impacts of celebrity credibility and advertising skepticism on purchase intention in response to various desirable/undesirable endorsers. Moreover, the TPP would decrease the impact of celebrity credibility, but increase the impact of advertising skepticism on purchase intention, indicating that the third persons' attitudes toward CEA may become a key reference in consumers' purchase intention processes.